Prediction of Postoperative Ileus in Patients With Colorectal Cancer by Preoperative Gut Microbiota - Jin, Ye; Geng, Rui; Liu, Yang; Liu, Lujia; Jin, Xiangren; Zhao, Fuya; Feng, Jing; Wei, Yunwei (Frontiers in Oncology, 2020)
Background: Ileus and postoperative ileus are common complications of colorectal cancer (CRC). However, little is known about the gut microbiota associated with ileus. Method: Differences in gut microbiota were evaluated by 16S rRNA gene sequencing. We characterized the gut microbiota in 85 CRC patients (cohort 1) and detected differences, and an independent cohort composed of 38 CRC patients (cohort 2) was used to evaluate the results. Results: The gut microbiota of CRC patients with and without ileus exhibited large differences in alpha- and beta-diversities and bacterial taxa. The Firmicutes to Bacteroidetes ratio and microbial dysbiosis index showed greater dysbiosis among ileus patients than among those without ileus. According to the location of CRC, the difference in gut microbiota between patients with and without ileus was more obvious in those with distal CRC than in those with proximal CRC. Finally, Faecalibacterium was significantly reduced in the postoperative perioperative period in patients with ileus. Thus, we used Faecalibacterium as a biomarker for predicting perioperative or postoperative ileus: the AUC value was 0.74 for perioperative ileus and 0.67 for postoperative ileus that appeared at six months after hospital discharge. The predictive power was evaluated in Cohort 2, with an AUC value of 0.79. Conclusion: These findings regarding changes in gut microbiota in postoperative CRC patients may allow the use of microbiota as biomarkers for predicting postoperative ileus.